2006
DOI: 10.1016/j.jacc.2005.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Markers of Atherosclerosis in Human Immunodeficiency Virus-Infected Patients

Abstract: The data of the present study suggest an increased cardiovascular risk in HIV-infected patients, even in the absence of clustering of metabolic risk variables. The presence of the MS in HIV is associated with even more advanced atherosclerotic changes. Presumably, both HIV infection and antiretroviral therapy may promote atherosclerosis through mechanisms involving endothelial cells, either directly or indirectly via metabolic risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
7
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 37 publications
3
76
7
2
Order By: Relevance
“…The Data Collection on Adverse Events of Anti-HIV Drugs (DAD) study reported that cumulative protease inhibitor exposure is an independent risk factor for MI [2], but the risk of specific protease inhibitors on MI incidence or surrogate measures of cardiovascular disease risk has not been well characterized. Although the HIV-infected subjects in the present study had considerable cumulative length of time on HAART, the brachial FMD was higher than in other crosssectional studies of HIV-infected persons [10][11][12][13] and similar to that of normal controls; CIMT was also similar in both groups. These findings may be due, in part, to the long-term use of modern, metabolically 'friendly' antiretroviral regimens [30].…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…The Data Collection on Adverse Events of Anti-HIV Drugs (DAD) study reported that cumulative protease inhibitor exposure is an independent risk factor for MI [2], but the risk of specific protease inhibitors on MI incidence or surrogate measures of cardiovascular disease risk has not been well characterized. Although the HIV-infected subjects in the present study had considerable cumulative length of time on HAART, the brachial FMD was higher than in other crosssectional studies of HIV-infected persons [10][11][12][13] and similar to that of normal controls; CIMT was also similar in both groups. These findings may be due, in part, to the long-term use of modern, metabolically 'friendly' antiretroviral regimens [30].…”
Section: Discussioncontrasting
confidence: 69%
“…This study was cross-sectional and the number of subjects was low, but still higher compared with several other endothelial function studies in HIV [11][12][13]36]. In addition, several HIV-infected subjects were on statin therapy, which may have a positive effect on brachial FMD and CIMT.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Using femoral PWV, previous studies showed increased aortic (central) stiffness in treated39 and untreated9 HIV-infected individuals. In our study, the peripheral cr-PWV did not differ between the HIV-infected participants and their age-, gender-, BMI- and locality-matched controls.…”
Section: Discussionmentioning
confidence: 99%
“…Embora haja evidências de que os pacientes com HIV apresentem maior risco de infarto do miocárdio do que a população geral (15), não há dados sobre a associação de SM com o risco cardiovascular nesses pacientes. Um estudo mostrou que a espessura íntima-média da carótida, um marcador intermediário de risco cardiovascular, estava aumentada em pacientes infectados por HIV com SM, de maneira similar à observada em diabéticos não-infectados (33). Entretanto, estudos prospectivos ainda são necessários para esclarecer o impacto da SM sobre os desfechos clíni-cos (eventos cardiovasculares e morte) nessa população.…”
Section: Diehl Et Alunclassified